Signaling System in Porphyromonas gingivalis Based on a LuxS Protein - Chung, Whasun O. (American Society for Microbiology, 2001)
The luxS gene of quorum-sensing Vibrio harveyi is required for type 2 autoinducer production. We identified a Porphyromonas gingivalis open reading frame encoding a predicted peptide of 161 aa that shares 29% identity with the amino acid sequence of the LuxS protein of V. harveyi. Conditioned medium from a late-log-phase P. gingivalis culture induced the luciferase operon of V. harveyi, but that from a luxS insertional mutant did not. In P. gingivalis, the expression of luxS mRNA was environmentally controlled and varied according to the cell density and the osmolarity of the culture medium. In addition, differential display PCR showed that the inactivation of P. gingivalis luxS resulted in up-regulation of a hemin acquisition protein and an arginine-specific protease and reduced expression of a hemin-regulated protein, a TonB homologue, and an excinuclease. The data suggest that the luxS gene in P. gingivalis may function to control the expression of genes involved in the acquisition of hemin.